INSTAGRAM CONTENT EXPOSURE @JASTIP_DONGKA AND FOLLOWERS' CONSUMER BEHAVIOR PATTERNS - Rahmadini, Chika Laily; Sangun , Enisar; Sari , Natalina Nilam (Universitas prof. Dr. Moestopo (Beragama), 2025)
This study aims to examine the extent to which social media content exposure influences consumer behavior patterns, using DeFleur's media dependency theory as the analytical framework. This theory explains that the relationship between mass media and individuals or society is dynamic and mutually influential, meaning that exposure to social media content has the potential to shape users' consumption habits. As individuals increasingly rely on social media for information and recommendations, their purchasing decisions may be influenced by the content they frequently engage with. To test this influence, the study employs a survey method by distributing questionnaires to 132 respondents who are followers of the Instagram account @jastip_dongka. This account specializes in offering online shopping services, making its followers relevant subjects for analyzing how social media exposure shapes consumer behavior. Through this survey, four main indicators of the independent variable (X) were analyzed: frequency, duration, interaction, and content type consumed. The findings indicate that all four indicators significantly impact the dependent variable (Y), which is consumptive behavior patterns. Furthermore, the study measures the overall contribution of these indicators to shaping consumptive behavior, which accounts for 29.2%, while the remaining 70.8% is influenced by factors not examined in this research.